Alternative Design of Menara 17 Structure in Surabaya with Castellated Steel Beam - Febriawan, Mochamad Rizaldi; Astawa, Made Dharma; Sumaidi, Sumaidi (CIVED, 2023)
Assigning structural material is one of critical step in designing, steel material often used because of it high ductility. Menara 17 is a 17 storey multipurpose building with reinforced concrete as an existing material structure. This research analyze Menara 17 alternative design with Special Moment Frame (SMF) steel structure to resist lateral load with high ductility and expected to withstand significant inelastic deformation. Castellated beam is used to increase it capacity to weight ratio and ease MEP installation through the opening. SNI and AISC is used for main design guide. From the analysis result, the alternative design has satisfy criteria of irregularity, P-delta effect, story drift, and Strong Column Weak Beam. Honeycomb castellated beam HCO 520.250.9.14 profile is used as main beam. King-cross column KC 800.400.16.30 profile is used as main column. Circular hollow section CHS 406,4.40 profile is used as diagonal bracing. Wide flange WF 200.200.8.12 profile is used as lateral bracing. Lateral bracing to beam is connected with shear connection. Beam to column is connected with endplate moment connection. Menara 17 design with steel structure is 59,17% less heavy than reinforced concrete structure.